Beban Kognitif Siswa Pada Pembelajaran Kimia: Survey Terhadap Pelajar Sekolah Menengah Atas di Indonesia - Sela Marselyana Abadi; Irwanto; Afrizal (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the cognitive load of students in chemistry learning and categorize the results based on grade levels. The research was conducted in the form of a survey using a quantitative approach during the second semester of the 2023/2024 academic year. The sample was taken using simple random sampling technique and consisted of 600 students from 10 public high schools and 5 private high schools from DKI Jakarta, Banten, West Java, and South Sumatra Province. The instrument used was a cognitive load questionnaire to measure two aspects of cognitive load: mental load and mental effort. Data analysis was performed using descriptive statistics and one-way ANOVA test. The findings indicate that the overall cognitive load of students is in the moderate category (M = 23.29), suggesting that most students can process the learning materials. Mental load (M = 2.92) was found to be slightly higher than mental effort (M = 2.90), implying that students experience greater cognitive demands in understanding concepts than in performing tasks. Grade X students showed the highest cognitive load, likely due to their novice-level understanding of abstract chemical concepts. The results also highlight that cognitive load can be managed and maintained at a moderate level through appropriate instructional strategies and supportive learning environments.